Message relay system for mobile ad hoc networks - Baylon, Kristina Jane (2006)
The aim of this research is to develop a message relay system that allows message passing through four or more mobile devices, as well as an implementation of PISO over this system. this project is aimed at taking advantage of the increasing popularity of Wi-Fi enabled mobile devices. The first phase of the research focused on finding a way to allow for relay involving more than three devices, thus surpassing the three-node limit imposed by mobile device hardware limitations. The second phase dealt with creating an implementation of the PISO protocol over the relay system, specifically providing mechanisms for route discovery, route maintenance, and handling for failed routes. The final phase of the research involved testing the relay system and the protocol for relay capabilities and losses. The end product, Wi-G, is a functional application that works over the message relay system and protocol, able to adopt to changes in network topology in order to properly deliver messages over the network. Finally, this research provides valuable information regarding different factors that affect network performance, as well as recommendations on what steps should be taken next.